The girl who lost her shadow - Ilett, Emily (Kelpies, 2020)
On the morning of her birthday, Gail's shadow leaves her along with her sister Kay's. It is just one more abandonment that has happened after her father leaving the family and her older sister sinking into sadness. In hopes of fixing her sister, Gail decides to search for the two shadows which takes her on an unexpected adventure into a world of light and shadow where hope and despair sit next to each other.